321 Comparison of two types of triple incision technique in the treatment of patients with locally advanced vulvar cancer. (13th November 2020) - Wu, M; Li, J; Ma, Y; Lin, Z
Abstract : Objective: We proposed a modified triple incision technique (MTIT) for vulvar cancer patients with locally advanced disease and reported it in 2002. MTIT has gone through a series of modification and a modified MTIT (M-MTIT) came into being. The purpose of this study was to introduce M-MTIT and compare it with MTIT. Methods: 57 vulvar cancer patients with clinical stage T2 (>4 cm) or T3 disease were included. Of them, 28 underwent MTIT and 29 underwent M-MTIT. Their data on surgery-related complications and survival outcomes were compared. Results: The patients treated with M-MTIT developed significantly less surgery-related morbidities than patients treated with MTIT (24.1% vs. 60.7%, P = 0.005). Wound breakdown was the most common complication in our cohort, which occurred less frequently in the M-MTIT group than in the MTIT group (10.3% vs. 35.7%, P = 0.022). Multivariate logistic regression analysis identified M-MTIT as an independent predictor of reduced risk of wound breakdown. The incidence of other complications, including lymphedema, wound infection and cellulitis was lower in M-MTIT group than in MTIT group; however, the differences did not reach statistical significance. Median follow-up time of this study was 33 months. The Kaplan-Meier survival graphs did not show significant differences in recurrence-free survival and overall survival between the two groups. Conclusions: M-MTIT correlates with lower morbidity rates and does not compromise oncological safety compared with MTIT. It could be considered as a safe and feasible option for vulvar cancer patients with locally advanced disease.